2020
DOI: 10.1186/s41100-020-00289-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between modified simple protein-energy wasting (PEW) score and all-cause mortality in patients receiving maintenance hemodialysis

Abstract: Background: Protein-energy wasting (PEW) is a frequently observed complication that leads to increased mortality in hemodialysis patients. However, a multifaceted assessment of PEW by combined objective nutritional parameters has not yet been established. Methods: In total, 144 Japanese patients receiving maintenance hemodialysis at a hemodialysis center were retrospectively followed for 7 years. The primary outcome was all-cause death. The main exposure was a modified simple PEW score (0, 1, 2, 3, or 4), calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The panel of the International Society of Renal Nutrition and Metabolism proposed four components of PEW for multifaceted assessment of nutritional status: (i) biochemical indicators such as albumin or pre-albumin; (ii) low body weight, reduced fat, or weight loss; (iii) decreased muscle mass; and (iv) low protein or energy intake [57]. We and others have shown that a low PEW score, which includes one of the definitions for each component, is associated with an elevated risk of all-cause mortality and can be used as an assessment tool [62,63]. Another useful tool for assessment of nutritional status is the nutritional risk index for Japanese hemodialysis patients (NRI-JH), created using a large database of Japanese hemodialysis patients [64].…”
Section: Assessment Of Nutritional and Inflammatory Status In Ckd/hem...mentioning
confidence: 99%
“…The panel of the International Society of Renal Nutrition and Metabolism proposed four components of PEW for multifaceted assessment of nutritional status: (i) biochemical indicators such as albumin or pre-albumin; (ii) low body weight, reduced fat, or weight loss; (iii) decreased muscle mass; and (iv) low protein or energy intake [57]. We and others have shown that a low PEW score, which includes one of the definitions for each component, is associated with an elevated risk of all-cause mortality and can be used as an assessment tool [62,63]. Another useful tool for assessment of nutritional status is the nutritional risk index for Japanese hemodialysis patients (NRI-JH), created using a large database of Japanese hemodialysis patients [64].…”
Section: Assessment Of Nutritional and Inflammatory Status In Ckd/hem...mentioning
confidence: 99%
“…Accumulating evidence has shown that GNRI is a good surrogate marker of nutritional status, and that GNRI is a predictor of comorbidities and mortality in patients receiving hemodialysis or peritoneal dialysis [9–13]. A recent meta‐analysis pooled data for 10 739 patients from 19 cohort studies published between 2010 and 2018 [17].…”
Section: Discussionmentioning
confidence: 99%
“…The four knots of the spline curves were the 5th, 35th, 65th, and 95th percentiles. To compare the predictability performance for all-cause mortality between the original GNRI and the sGNRI-10, we calculated the area under the receiver operating characteristic curve (AUROC), net reclassification improvement (NRI), and integrated discrimination improvement (IDI) [13,16]. AUROCs of the original GNRI and the sGNRI-10 were compared by DeLong's test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cut-off values are as follow: nPCR 0.8 g/kg/day, serum albumin 38 g/L, serum Cr/BSA 380 μmol/L/m 2 ( 14 , 15 ). Due to small body size of the study population, the cut-off value of < 18 kg/m 2 for the BMI was selected based on its association with increased mortality in Japanese hemodialysis patients ( 16 , 17 ). BSA was calculated using DuBois & DuBois equation: 0.20247 × height (m) 0 .…”
Section: Methodsmentioning
confidence: 99%